The revival of the Griesbach hypothesis: an analysis and appraisal - Tuckett, C. (Society for New Testament Studies monograph series, 1983)
There has recently been strong support for the hypothesis that, contrary to the formerly accepted view that Mark's gospel was the first to be written, Mark was in fact the last synoptic gospel to appear. This book is a detailed examination of the arguments used to support this view, which constitutes a revival of that put forward by J. J. Griesbach at the end of the eighteenth century. Since Markan priority and the Two-Document hypothesis have been basic presuppositions for much modern gospel study, all attempts to question them must be taken very seriously. Dr Tuckett does this by investigating the redactional activity each hypothesis presupposes, and by then asking which source theory provides the most rational and consistent account of the redactional process.